Evaluation of Antibiotics Residues in Chicken Meat Samples in Lebanon - Adla Jammoul; Nada El Darra (MDPI AG, 2019)
Antibiotic residue in chicken is a human health concern due to its harmful effects on consumer health. This study aims at screening the antibiotic residues from 80 chicken samples collected from farms located in different regions of Lebanon. An optimized multi-class method for identification and quantification of 30 antibiotics from four different chemical classes (sulfonamides, tetracyclines, quinolones, and beta-lactams) has been developed by using liquid chromatography−mass spectrometry. The evaluation of antibiotics residues in 80 chicken muscles samples has shown that 77.5% of samples were at least contaminated with antibiotics residues, out of which 53.75% were exposed to co-occurrence of multidrug residues. The screening of the four antibiotics families has shown that ciprofloxacin (quinolones) represents the highest occurrence percentage (32.5%), followed by amoxicillin (β-lactams) (22.5%) and then tetracyclines (17.5%). Means of sarafloxacin, amoxicillin, and penicillin G residues levels were above the Maximum Residue Limit (MRL) recommended limit according to the European Union EC. This study revealed that chicken samples collected from Lebanese farms contain antibiotic residues. Guidelines for prudent use of antimicrobials agents for chicken should be adopted to reduce the prevalence of resistant Salmonella in chicken.